Avaliação do gasto energético de repouso em pacientes com sepse associada ou não à lesão renal aguda - Sanches, Ana Cláudia Soncini [UNESP] (2016)
Abstract Background: The determination of resting energy expenditure (REE) in critically ill patients is essential to prevent complications such as hypo and hyper alimentation. Objectives: This study aims to describe the REE in septic patients with and without acute kidney injury (AKI) and compare the REE estimated by the Harris-Benedict equation (HB) with the REE measured by indirect calorimetry (IC). Methods: Prospective and observational study was performed for 18 consecutive months. Septic patients older than 18 years, undergoing mechanical ventilation, with or without AKI defined by KDIGO criteria, and admitted to the Intensive Care Unit of University Hospital from Brazil were included. The REE was estimated by HB equation and measured by the IC within 72 hours after the diagnosis of sepsis and seven days after the initial measure. The chi-square test was used to compare categorical variables and t-test to compare parametric variables. For non-parametric variables, the Mann-Whitney test was used, p<0.05. Variables with significant univariate associations (p<0.10) were candidates for multivariable analysis, which was performed using stepwise variable selection. Repeated measures analysis using the mixed procedure was used for the evolutional REE. Results: Sixty-eight patients were evaluated, age was 62.49 ± 16.6 years, 64.7% were male, 63.2% had AKI, and SOFA was 9.81 ± 2.35. The measured REE was 1857.53 ± 685.32 kcal, while the estimated REE was 1514.87 ± 356.72 kcal, with adequacy of 123.49 ± 43%. Septic patients without AKI (n = 25) and with AKI (n = 43) had measured GER statistically higher than the estimated one (1855.0 kcal (1631.75-2052.75) vs. 1551.0 (1349.0 -1719.25), p = 0.007 and 1868.0 kcal (1219.5-2364 75) vs. 1388.0 kcal (1254.0-1665.5), p = 0.026, respectively). There was no significant difference between the two groups (with and without AKI) in measured and estimated REE (p = 0.6268 and 0.6360, respectively). There was no significant difference in evolutional REE (1845.955 ± 658.273 kcal vs. 1809.545 ± 755.083 kcal, p = 0.865). Conclusion: The REE measured by IC was significantly higher than that estimated by the equation HB in both septic with and without AKI. There was no significant difference between the septic patients with and without AKI in REE, suggesting that AKI does not influence the energy metabolism of septic patients.